Magnetic resonance imaging of brain structural and functional changes in cognitive impairment associated with Parkinson’s disease - Cao, Danna; Yue, Jinhuan; Wei, Zeyi; Huang, Dong-Hong; Sun, Xuchen; Liu, Ke-Xuan; Wang, Peng; Jiang, Fan; Li, Xiaoling; Zhang, Qinhong (Frontiers in Aging Neuroscience, 2024)
Cognitive impairment is a critical non-motor symptom of Parkinson’s Disease (PD) that profoundly affects patients’ quality of life. Magnetic Resonance Imaging (MRI) has emerged as a valuable tool for investigating the structural and functional brain changes associated with cognitive impairment in PD (PD-CI). MRI techniques enable the precise identification and monitoring of the onset and progression of cognitive deficits in PD. This review synthesizes recent literature on the use of MRI-based techniques, including voxel-based morphometry, diffusion tensor imaging, and functional MRI, in the study of PD-CI. By examining these imaging modalities, the article aims to elucidate the patterns of brain structural and functional alterations in PD-CI, offering critical insights that can inform clinical management and therapeutic strategies. In particular, this review provides a novel synthesis of recent advancements in understanding how specific MRI metrics, such as amplitude of low-frequency fluctuations, regional homogeneity, and functional connectivity, contribute to early detection and personalized treatment approaches for PD-CI. The integration of findings from these studies enhances our understanding of the neural mechanisms underlying cognitive impairment in PD and highlights the potential of MRI as a supportive tool in the clinical assessment and treatment of PD-CI.